2023
DOI: 10.3390/f14040808
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soil–Water Characteristics and Stability Evolution of Rainfall-Induced Landslide: A Case of the Siwan Village Landslide

Abstract: This paper aimed to study the soil–water characteristics and stability evolution law of rainfall-induced landslide. Taking the two landslide events in Siwan village as an example, the formation conditions of the disaster and landslide characteristics were analyzed. Additionally, the deformation characteristics and destruction mechanisms of landslides were discussed in-depth. The soil–water characteristics and hydraulic conductivity of the landslides were analyzed based on TRIM experiment results. Geo-Studio nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…A comparison of the safety factor values of research by (Shah et al, 2021) with the development of analysis in this study is shown in Table 3 below. LEM and FEM analyses reveal that the safety factor is higher in dry slopes compared to saturated conditions, aligning with research by (Wen et al, 2023) During rainfall, stability conditions can rapidly decrease, leading to landslides due to potential slip plane development. Supplementary parameters, including the material shear strength factor in the LEM analysis, yield consistent results, as illustrated in Figure 8 below.…”
Section: Resultssupporting
confidence: 85%
“…A comparison of the safety factor values of research by (Shah et al, 2021) with the development of analysis in this study is shown in Table 3 below. LEM and FEM analyses reveal that the safety factor is higher in dry slopes compared to saturated conditions, aligning with research by (Wen et al, 2023) During rainfall, stability conditions can rapidly decrease, leading to landslides due to potential slip plane development. Supplementary parameters, including the material shear strength factor in the LEM analysis, yield consistent results, as illustrated in Figure 8 below.…”
Section: Resultssupporting
confidence: 85%
“…The process of loose accumulation landslides occurs in unsaturated soil conditions (Wu et al, 2018;Yamaguchi et al, 2023). As research on the stability of unsaturated soil landslides progresses, there is a growing need for quantitative analysis of rainfall infiltration patterns and the processes of deformation and failure under unsaturated conditions (Chen and Lee, 2003;Ding et al, 2006;Ma et al, 2017;Zhao et al, 2022;Paswan and Shrivastava, 2023;Wen et al, 2023). Lin et al (2009) delved into the intricate interplay between rainfall characteristics and slope instability through meticulous artificial rainfall model tests.…”
Section: Introductionmentioning
confidence: 99%